196k views
5 votes
2(9n-1)+7(n+6)=-60

what is this answer

User HHeckner
by
5.6k points

2 Answers

4 votes

Answer:

n=-4

Explanation:

2 (9n-1)+7(n+6)= -60

18n-2 +7n + 42 = -60

25n + 40 = -60

25n = -100

n = -4

User Amjad Abujamous
by
5.0k points
2 votes

Answer:

n = - 4

Explanation:

2 ( 9n - 1 ) + 7 ( n + 6 ) = - 60

Solve the brackets.

18n - 2 + 7n + 42 = - 60

Combine like terms.

25n + 40 = - 60

Subtract 40 from both sides.

25n = - 60 - 40

25n = - 100

Subtract 25 from both sides.

n = -4

User Vannessa
by
4.7k points